Localizing A Global Brand: Starbucks’s Marketing Strategy In China - Huang, Qingyi (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2025)
With the acceleration of economic globalization, cultural integration and innovation across countries have become increasingly prominent. Coffee culture is also becoming more integrated into the consumption needs of the Chinese market. Since Starbucks entered China in 1998, its marketing strategy has achieved remarkable results, becoming a successful example of international brand localization. This paper aims to analyze the development of Starbucks in China and explore how it has adjusted its marketing strategies to achieve cultural localization, thereby establishing a firm foothold in the local market and becoming its most important overseas market after the United States. This study adopts a combination of literature review and comparative analysis methods, collecting a large amount of relevant research materials and applying SWOT analysis theory to identify the strengths, weaknesses, opportunities, and threats of Starbucks' marketing strategy. The findings indicate that Starbucks' success lies in its effective adaptation to Chinese consumer preferences, brand positioning, and cultural localization. However, challenges such as intensified market competition and market saturation still exist. This research aims to serve as a reference for other food and beverage companies seeking to enter emerging markets.